Information Media about Pain Management for Infants in Ungaran Public Health Center - Mona Saparwati; Trimawati Trimawati (Humanistic Network for Science and Technology (HNST), 2018)
Immunization is one of the acute painful procedures and cause trauma in infant. Non pharmacologic intervention is pain management 5 (swaddling, side/stomach position, shushing, swinging, sucking). More of moms and parent not understanding about pain management at infant after giving imunization. The purpose of this study was to identify the moms level understanding, so that will be developed information media abaout pain management in infant. The method used are two stage. The first stage to identified respondent characteristic and external factor about moms understanded pain management at infant after immunization and than maked information media. The second stage to tried the animation video about pain management 5S information media. The method used in quasy experiment with pretest postes control group design. The sampling used in 30 moms wint infant get immunization in Ungaran Public Health. Data collected at pre and post test. Then tested by Mann Withnew test.The result showed more respondent (83.3%) at education he results showed that some respondents (83.3%) belonged to the productive age (20-35 years), with the most high school education. The results showed that some respondents had less knowledge about the pain of babies after getting immunizations and how to deal with baby's pain after immunization. Media information expected by respondents is video. There is an effect of the animated video of 5S pain management on infants on understanding 5S pain management in infants in Ungaran Health Center (p value = 0.000). Information media in the form of animated videos is precisely used to improve maternal understanding of 5S pain management in infants.Keywords: Pain management, Information media, Infant